A Strategic planning for the implementation of religious moderation at Al-Ma'arif Institute in Way Kanan District - Novari, Deka Meuthia; Pahrudin, Agus; Syafril, Syafrimen; Koderi, Koderi (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This proposes is a strategic plan for fostering religious moderation within the Al-Ma'arif Institute in Way Kanan District, Indonesia. The plan aims to cultivate a tolerant and inclusive learning environment that embraces diversity and promotes peaceful coexistence among students and staff. Research methodology: The research employs a qualitative approach, utilizing in-depth interviews, focus group discussions, and document analysis to gather data on existing religious practices and attitudes within the Institute. The insights gained inform the development of a strategic framework encompassing key areas such as curriculum development, teacher training, student engagement activities, and community outreach initiatives. Results: The anticipated outcomes of implementing the strategic plan include enhanced understanding and appreciation for diverse religious perspectives among students and teachers., development of peaceful and tolerant campus culture that respects individual beliefs, improved community relations and contributions to fostering religious harmony in Way Kanan District. Contribution: This research offers a valuable roadmap for educational institutions seeking to promote religious moderation within their communities. The strategic plan, tailored to the specific context of the Al-Ma'arif Institute, provides a practical framework that can be adapted and applied by other institutions in diverse settings. The success of implementing this plan can serve as a model for fostering peaceful and inclusive learning environments that contribute to broader societal harmony.